Computerized Morphometric Analysis of Human Femoral Articular Cartilage. (15th February 2012) - Goyal, Neeru; Gupta, Madhur
Abstract : Objective . Articular cartilage shows changes with age that are considered to be the most important factors in the development and progression of osteoarthritis. The studies on age changes in articular cartilage have been traditionally based on individual observations but this approach is limited by its subjectivity and bias, yielding considerable variability. So the present study was conducted to observe various age related changes in morphology of femoral articular cartilage using computerized morphometric analysis. Design . The articular cartilage specimens were divided into two groups according to age: group 1 (n = 16 ) below 40 years (16–40 years) and group 2 (n = 12 ) above 40 years (41–86 years) of age. 5  μ m thick paraffin sections were stained with H&E and analyzed using Image Pro Express image analysis software for quantitative analysis of articular cartilage. Various parameters, that is, total thickness of the cartilage, area of lacunae in each zone, area of subchondral cavities, and number of chondrocytes per 10, 000  μ m 2 area in each zone were measured. Results . Significant difference with age was found in the total thickness and area of lacunae in zone 3. Conclusions . Not much difference is observed in articular cartilage morphology with age. So ageing is not the only risk factor in development of osteoarthritis.